The fusion subunit vaccine L-DBF protects aged mice against heterologous lethal Shigella challenge after prior exposure - Parvej, Md Shafiullah; Lu, Ti; Maiti, Suhrid; Dietz, Zackary K.; Howlader, Debaki R.; Zahan, Mst Nusrat; Cato, Alexa; Biswas, Satabdi; Picking, William D.; Picking, Wendy L. (Frontiers in Immunology, 2025)
Shigellosis is among the top causes of bacterial diarrhea with significantly high morbidity and mortality for children under five years of age in low- and middle-income countries. Unfortunately, there are currently no licensed vaccines to prevent shigellosis. Our laboratory has developed the protein-based subunit vaccine candidate L-DBF by fusing the type III secretion system proteins IpaB and IpaD with the mucosal adjuvant LTA1, the active moiety of the heat-labile toxin from enterotoxigenic Escherichia coli. L-DBF delivered intranasally has been shown to protect against multiple serotypes of Shigella using the lethal pulmonary mice model. In recent work, we showed that even following prior infection with two sublethal doses of S. flexneri 2a in adult mice, L-DBF effectively cross-protects mice from a potentially lethal challenge with S. sonnei in addition to S. flexneri. We therefore wanted to know whether a prior sublethal infection by S. flexneri or S. sonnei would impact the protective immune response elicited by L-DBF against heterologous lethal infections in an aged mouse model. Elderly mice were subjected to a single sublethal dose of S. flexneri or S. sonnei prior to vaccination with L-DBF. We found that pre-exposed mice receiving L-DBF developed heterologous cross-protection against both S. flexneri and S. sonnei lethal challenge doses. This contrasts with unvaccinated mice that succumbed to the lethal challenge, despite a single homologous or heterologous pre-exposure to Shigella spp. Thus, L-DBF is a strong candidate for a protective shigellosis vaccine in all age groups to protect against commonly encountered Shigella serotypes in both naïve hosts and those pre-exposed with homologous or heterologous Shigella serotypes.